Association between smoke-free workplace and second-hand smoke exposure at home in India. Issue 4 (23rd March 2013) - Lee, John Tayu; Agrawal, Sutapa; Basu, Sanjay; Glantz, Stanton A; Millett, Christopher
Abstract : Background: The implementation of comprehensive smoke-free laws has been associated with reductions in second-hand smoke exposure at home in several high income countries. There is little information on whether these benefits extend to low income and middle income countries with a growing tobacco-related disease burden such as India. Methods: State and individual-level analysis of cross-sectional data from the Global Adult Tobacco Survey India, 2009/2010. Associations between working in a smoke-free indoor environment and living in a smoke-free home were examined using correlation at the state level, and multivariate logistic regression at the individual level. Results: The percentage of respondents employed indoors (outside the home) working in smoke-free environments who lived in a smoke-free home was 64.0% compared with 41.7% of those who worked where smoking occurred. Indian states with higher proportions of smoke-free workplaces had higher proportions of smoke-free homes (rs =0.54, p<0.005). In the individual-level analysis, working in a smoke-free workplace was associated with a significantly higher likelihood of living in a smoke-free home (adjusted OR=2.07; 95% CI 1.64 to 2.52) after adjustment for potential confounders. Conclusions: Implementation of smoke-free legislation in India was associated with a higher proportion of adults reporting a smoke-free home. These findings further strengthen the case for accelerated implementation of Article 8 of the Framework Convention on Tobacco Control (FCTC) in low and middle income countries.